Preserving Dryland Forests and Agrosilvopastoral Systems: Sustainable Rangeland Management at the Committee on Forestry (COFO) - Spinelli, Madison; Louhaichi, Mounir (International Livestock Research Institute, 2023)
Covering 41% of Earth's land, drylands are home to nearly 2 billion people relying on forests, rangelands, and agrosilvopastoral systems for survival. These areas provide crucial environmental services, supporting biodiversity, preventing erosion, averting land degradation, enhancing water infiltration, and boosting soil fertility. Amid global change, they serve as resilient landscapes and communities. From September 10th to 13th, 2023, the 3rd COFO session in Amman, Jordan, united experts and stakeholders, addressing the degradation and restoration of dryland forests and agrosilvopastoral systems. Emphasizing a holistic approach, the session underscored the need to integrate ecological, social, and economic factors, focusing on biodiversity, soil health, and community engagement. ICARDA, in collaboration with IUCN, championed this cause with the Sustainable Rangeland Management Toolkit. Presented by Mounir Louhaichi, the toolkit advocates a multi-stakeholder approach, incorporating genebanks, agro-biodiversity, and innovative technologies to address challenges posed by water scarcity and climate variability. The COFO session advocated for regional agro-biodiversity, improved land management, and the toolkit's implementation, offering a clear path for preserving critical ecosystems. Beyond environmental imperatives, preserving dryland forests and agrosilvopastoral systems is a social and economic necessity, vital for food, livelihoods, and biodiversity. The toolkit underscores a comprehensive approach, actively involving local communities in decision-making. Mounir Louhaichi's participation exemplifies the commitment to addressing challenges in dryland regions, emphasizing the interconnectedness of land management, climate change, and sustainable agriculture. COFO provided an opportunity to enhance regional agro-biodiversity and improve dryland agrosilvopastoral systems through the toolkit and innovative technologies.